2019
DOI: 10.18502/fid.v16i3.1593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcium Hypochlorite and Sodium Hypochlorite, as Root Canal Irrigants, on the Bond Strength of Glass Fiber Posts Cemented with Self-Adhesive Resin Cement

Abstract: Objectives:Calcium hypochlorite (Ca(OCl)2) is currently used as a root canal irrigant. The aim of this study was to compare the effects of calcium hypochlorite and sodium hypochlorite (NaOCl), as root canal irrigants, on the bond strength of posts cemented with a self-adhesive resin cement.Materials and Methods:In this in-vitro study, 40 maxillary central incisors with similar root lengths were decoronated. The teeth were randomly divided into five groups based on the irrigant used: Group 1: normal saline (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Studies using self-adhesives as luting material for glass fiber posts showed similar results in all three root regions (cervical, middle, and apical). [ 30 31 32 33 ] However, this differs from the findings obtained in the present study, since a significantly higher bond strength was obtained in the apical region when the post surface was pretreated with 37% phosphoric acid and 1.23% APF, coinciding with the reports of Vildósola et al [ 34 ] and Boing et al [ 35 ] It is possible that the bond strength was better in the apical region because of root anatomy, since the glass fiber posts used in this study were conical in shape, making them better adapted to this region. In addition, the self-adhesive cement used (RelyX U200) showed, in other studies, better volume and fluidity at the apical region of root,[ 1 36 ] which favors good bonding.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using self-adhesives as luting material for glass fiber posts showed similar results in all three root regions (cervical, middle, and apical). [ 30 31 32 33 ] However, this differs from the findings obtained in the present study, since a significantly higher bond strength was obtained in the apical region when the post surface was pretreated with 37% phosphoric acid and 1.23% APF, coinciding with the reports of Vildósola et al [ 34 ] and Boing et al [ 35 ] It is possible that the bond strength was better in the apical region because of root anatomy, since the glass fiber posts used in this study were conical in shape, making them better adapted to this region. In addition, the self-adhesive cement used (RelyX U200) showed, in other studies, better volume and fluidity at the apical region of root,[ 1 36 ] which favors good bonding.…”
Section: Discussionmentioning
confidence: 99%
“…After irrigation of the root canals, these by-products tend to precipitate into the root dentin [17,23]. Considering that the adhesion mechanism of self-adhesive resin cements and conventional glass ionomer involves the chemical reaction with the calcium from the hydroxyapatite of the dentinal substrate, it is possible that a synergism of action between the precipitated residues of CH with these cementation systems occurred, increasing the bond strength values [13,30]. On the other hand, our results diverge from those shown by Seballos et al [31], but the concentration of CH used in our study was 6%, which crucially tends to provide greater precipitation of calcium hydroxide, compared to other solutions with lower concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these shortcomings, the use of 6% calcium hypochlorite (CH) solution (Ca(OCl) 2 ), which also has the ability to clarify tissues, has been purposed [11]. Although Ca(OCl) 2 has chlorine in its composition, more chemical stability compared to SH is observed, allowing a more gradual ionic dissociation which tends to minimize the impact on the adhesive interface with conventional resin cement [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Besides from NaOCl, other alternative irrigants able to dissolve organic content have been proposed and studied in the endodontic field over the years 67 69 . Irrigants such as calcium hypochlorite or chlorine dioxide have been for their organic dissolution capacity 70 , 71 . In fact, 5% chlorine dioxide has been reported to show interesting and comparable results, to NaOCl, in bond strength outcomes 69 .…”
Section: Discussionmentioning
confidence: 99%